2022
DOI: 10.1007/s10734-022-00878-w
|View full text |Cite|
|
Sign up to set email alerts
|

Exploring the effects of mobility and foreign nationality on internal career progression in universities

Abstract: This article explores how organizational mobility and foreign nationality affect a researcher’s chances of an internal career promotion in university systems that do not have rules preventing inbreeding and where teaching occurs mostly not in English but a local language. As a case study, we have examined the Flemish university system, the Dutch speaking part of Belgium, and developed expectations on the chances of promotion for mobile and foreign researchers compared to non-mobile and nationals. We use data f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…In the absence of a uniform research assessment system, institutions can tailor assessment strategies to their needs. However, differences between assessment systems that are uniform at a national level pose a challenge for international mobility [40]. Potential obstacles are a particular issue for early-career researchers (ECRs) from scienti cally weakly-developed countries, for whom international experience makes a large difference [41].…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of a uniform research assessment system, institutions can tailor assessment strategies to their needs. However, differences between assessment systems that are uniform at a national level pose a challenge for international mobility [40]. Potential obstacles are a particular issue for early-career researchers (ECRs) from scienti cally weakly-developed countries, for whom international experience makes a large difference [41].…”
Section: Discussionmentioning
confidence: 99%
“…These types of engagement activities require a strong connection with the local market and recognition by the national economic players, including, for instance providing consultancy, carrying out research under contract, supervising students' internships with industry, and developing executive, tailor-made courses or programs. Some scholars have been discussing some negative effects of international mobility regarding the academics' re-integration into the home institution/system (Groves et al, 2018;Seeber et al, 2022). The stay abroad may hinder the establishment of a relationship with the local community, especially when the returning academics lack resources, facilities, and support from their institutions and colleagues, resulting in a kind of "isolation" from the local reality (Bauder, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…And while most of these institutions appreciate diversity, they are not, in fact, diverse at all. Statistics also prove this: for example, a study found that in Belgium, 21.9% of non-mobile post-docs became professors at Flemish universities, compared to internationally mobile (foreign) scholars, where the same rate was only 1.2% (Seeber, Debacker, Meoli & Vandevelde, 2022).…”
Section: The Exclusivist Environment Of Western Academiamentioning
confidence: 90%